Diagnosis of postoperative patients by use Auto regulation net and one role algorithm with integral data base . - Suhair Abd Dawood (College of Education for Pure Sciences, 2010)
Abstract The research aims to diagnosis the postoperative period of the patient.ın which an ıntegral database designed to contain personal ınformation, clinical checkup and examine the patient case after the surgery based on some properties (symptoms), which ıs regarded as ınputs of the database and results of three classification as outputs (patient prepared to go home, be sent to general hospital,be sent to the ıntensive care unit), by using neural network as classification algorithm connected with data mining algorithm (one rule) to reach the perfect classification through decreasing the properties of the original data and have one property sufficient to design a complete model,this system ıs programmed by using visual basic version 6 connected to database through microsoft access.